Heat and Mass Transfer Effects on Flow Past Parabolic Started Vertical Plate with Chemical Reaction and Thermal Radiation (Journal of Scientific Research, 2025)
In this paper an attempt has been made to study the unsteady flow past a parabolic starting motion of the infinite vertical plate, in the presence of heat source parameter, thermal radiation and chemical reaction. The plate   temperature and concentration level near the plate raised uniformly. The non-dimensional governing equations are solved with the help of Finite Difference method. The effects of   radiation, heat source parameter, chemical reaction, Schmidt number, Prandtl number on the characteristics of the flow are displayed graphically and the variation in skin friction, Nusselt number and Sherwood number are shown in table and the results are discussed. The result indicates that the rising values of thermal radiation and chemical reaction parameter decrease the fluid velocity. It is also found that temperature decreased under the eﬀect of the radiation parameter whereas chemical reaction contributes to decrease the concentration profile.